THE ROLE OF RELIGIUSITY AND PERSON ORGANIZATION FIT (POF) TO IMPROVE ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Heny Astuti; Heru Sulistyo (UNISSULA, 2017)
This study aims to analyze the role of satisfaction in mediating the correlation of religiosity and Person organization of Fit (POF) on Organizational Citizenship Behavior (OCB) more effectively. This research was inspired by the findings and empirical studies that show inconsistent results associated with the correlation values of employee spiritual level with organizational Citizenship Behavior (OCB) and organizational commitment. Religiosity and POF will be effective, if the value of religiosity and POF raises as intrinsic satisfaction. Employee satisfaction is a good approach to increase the level of motivation and contribution to organizational results. Satisfaction is expected to help solve the correlation of religiosity and POF on OCB more effectively.Keywords: Religiosity, Person Organization Fit (POF), Employee Satisfaction and Organizational Citizenship Behavior (OCB)